A glossary of cultural theory (Arnold, 2002)
"A Glossary of Cultural Theory provides the researcher and student with lucid and up-to-date guidance through the vibrant and changing debates in cultural studies and related disciplines. In a field where meanings are frequently complex and ambiguous, it has been highly praised for its clarity and helpfulness. This new edition has been updated throughout. Amongst the new terms are entries for Ecology, Everyday Life, The Event, Nomadism, Psychogeography and Taste, along with terms at the cutting edge of new thinking in social and cultural theory such as Convergeance, Cosmopolitanism, Cultural Intermediaries, the Posthuman, and Thirdspace. It is an ideal resource for everyone wishing to keep up to date with the changing agendas in cultural studies."--Jacket.